Pancasila Sebagai Landasan Filosofis Dalam Pembentukan Peraturan Perundang-Undangan - Nadya Shahnaz Gabriella; Akbar Ramadhan Gumas; Ardinia Awanis Shabrina; Febrianita Aisyah Putri (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
The aim of this research is to understand philosophically what is related to positive law in Indonesia, namely the idea of ​​Pancasila as the highest source of law in Indonesia (on a philosophical level, as a source set, law must not conflict with the idea of ​​Pancasila). The research method used in this research is normative research with a philosophical approach using secondary data as the main data. In this research, researchers used various literature consisting of various books, academic journals, and other academic works as secondary data sources. The data collection techniques and tools used in this research use the document method. Document research as a data collection tool can stand alone. This means that research can only use document research as the only data collection tool. The data analysis technique used in this research is inductive data analysis, namely drawing conclusions from actual facts in the field based on secondary data obtained. From the research results, it was found that the Pancasila ideology is the source of everything that exists in Indonesia, including the emergence of laws and regulations in Indonesia. The 1945 Constitution is the foundation of the state which contains fundamental norms including universal values. The 1945 Constitution is a document that contains the approval of all citizens. National harmony is summarized in the Pancasila ideology because the entire Indonesian nation is represented by the founding fathers and mother of the Indonesian nation. So basically Pancasila is the best source at a philosophical level in forming existing laws and regulations in Indonesia.